A sensor-based sun-tracking energy harvest system. (2015) - Tsai, Chia-Hung; Hu, Shu-Chiung; Huang, Chung-Hsiang; Tseng, Yu-Chee
Recent study has shown that the energy gain of a solar panel will be significantly influenced by the incidence angle of the sun radiation. The main goal of this paper is to present a sensor-based sun-tracking system. First, we design a sensing tower for measuring the direction of sun radiation. Then we design a sun-tracking algorithm, which adopts an iterative process to identify the direction of sun radiation to the earth's surface. This information is then passed to the nearby solar panels to adjust their angles. We have also developed a prototype and conducted several simulations to verify our sun-tracking system. Simulation results show that our system has better performance on the solar energy generation than existing ones.